(untitled) (Malay Literature, 2013)
Muhammad Haji Salleh is a famous Malaysian poet laureate as well as a foremost post-colonial intellectual. This article is a critical analysis of the persona and vision of the poet in his quest to construct his identity and to sustain the Malay language and literary heritage, as may be understood from his works and efforts since the 1970s. It is an expose of a laureate’s motivations behind his creativity. In dealing with Muhammad’s literary corpus, the article adopts a multi- and cross-disciplinary approach in combining literary criticism with elements of psychoanalysis, philosophy, politics, etc. These elements encapsulate the post-colonial quest of identity-forming, a subject that lies at the core of this article. The "empire writes back" perspective allows an in-depth analysis of motivation, migration and identity-formation as a way to reclaim resources -both tangible and intangible- from the colonisers. Thus, the discussion critically presents insights into the contexts and influences on Muhammad’s works, and in turn, his role in sustaining the Malay language and literary heritage. Keywords: Malay language, Malays literature, post-colonial quest, identity, Sustainability